PERAN AMERIKA SERIKAT DI KOSOVO PASCA KEMERDEKAAN KOSOVO - Lita Febriani; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
United State Role in Kosovo After the Kosovo’s Independent Day.  To be an independent day, Kosovo must face a many challenge, that’s  come from Serbia as a State which reject that aspiration. In other hand, United State show the good respon for this.  The purpose of this study is to know how United State Role in Kosovo. The hypothesis of this study is alleged there is a role of United State in Kosovo in Economy and Security field. This study is a qualitative research. It uses the library research method by taking the data from books, journals, articles and the internet. As a new State, Kosovo still need a help and support from the other State. United State play they role in Kosovo very well, it causes of United State have a national interest for their country.Keywords : Economy, Independence, National Interest, Role, Security